Research on Nursing of Patients with Mild Respiratory Infectious Diseases (Journal of Global Humanities and Social Sciences, 2024)
Objective: To explore the current home care programs and effects of patients with mild respiratory tract infections caused by influenza virus, Mycoplasma pneumoniae and novel coronavirus, so as to provide a reference for subsequent related research. Methods: PubMed, WebofScience core collection, China National Knowledge Infrastructure (CNKI), Wanfang Data and China Biology Medicine Database were searched by computer for literature screening, data extraction and summary on the existing home care programs and effects of patients with mild respiratory infectious diseases. Results: in 14 articles. Chinese researchers on defining the concept of mild and standard is a bit different, can be integrated to respiratory tract infection as the main performance, such as dry throat, sore throat, cough, fever, etc. Nursing programs generally included preventive nursing combined with health guidance intervention, personalized symptom nursing, cluster nursing, etc. Conclusion: the infection of respiratory tract infection caused by mild standard has not been unified, a direct impact on the late judge condition and formulate the related nursing operation timing, means and methods. At present, the commonly used nursing methods can effectively shorten the course of disease and relieve symptoms, but there is no specific mechanism research in the existing literature, and further exploration is needed to clarify its effect in the future.